2019
DOI: 10.3390/app9132676
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Crystallinity Development during Fused Filament Fabrication through Fast Scanning Chip Calorimetry

Abstract: Although semi-crystalline polymers are associated with considerably better mechanical properties and thermal stability compared to their amorphous counterparts, using them as feedstock for Fused Filament Fabrication still poses some major challenges. Hence, the development of printed part crystallinity during printing should be fully understood in order to control the developed weld strength, as well as part shrinkage and warpage. Infrared thermography was utilized to record the thermal history of deposited la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Another challenge to print PA6 is that they prone to warping. One of the reasons for warping is the semi-crystallinity of the PA6 polymers [26] , [27] , [28] , [29] . Another reason is the temperature differences through the thickness.…”
Section: Materials and Fff Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge to print PA6 is that they prone to warping. One of the reasons for warping is the semi-crystallinity of the PA6 polymers [26] , [27] , [28] , [29] . Another reason is the temperature differences through the thickness.…”
Section: Materials and Fff Processmentioning
confidence: 99%
“…A key reason for their limited use is attributed to their severe shrinkage and warpage that occurs during part cooling and crystallization. Polymers with high crystallinity distort and warp more during FFF process, in comparison with amorphous plastics, due to the considerable volume reduction associated with the formation of ordered, more densely packed regions during crystallization [26] , [27] , [28] . This causes parts that are fabricated with polyamide to warp more and detach from the build platform, compared to those with ABS [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate changes in physical-mechanical properties of the samples manufactured by 3D printing technology using PLA that is subsequently subjected to crystallization. Such studies have, of course, already been discussed by other researchers who indicated the positive effect of PLA crystallization on mechanical properties [5,6,[32][33][34]. Feng also discusses the impact of water absorption by the samples produced by the 3D method on their mechanical properties (which are known to be sensitive to water ageing).…”
Section: Introductionmentioning
confidence: 95%
“…Owing to the low viscosity and the self-healing character, the typical layer and line marks of the 3D-printing process (FFF) are not visible after printing, as is clearly shown in Figure 7b. Owing to the continued elevated temperature after deposition, due to both the heated bed and the deposition of layers on top, 41 the successive layers become covalently bonded to each other without the need of post-treatments. This allows to print airtight components, an important feature in soft pneumatic robotic systems.…”
Section: D Printingmentioning
confidence: 99%